Urban Policy in Times of Crisis: The Policy Capacity of European Cities and the Role of Multi-Level Governance. Issue 6 (November 2022) - Cucca, Roberta; Ranci, Costanzo
This article investigates how the policy capacity of urban governments in Europe to deal with the social challenges caused by the 2008-2009 financial crisis, has been strongly shaped by the institutional multi-level governance (MLG) settings in which cities were embedded. We consider the financial crisis as an important 'stress test' for urban policy. Urban governments faced a highly complex, trilemmatic situation: they faced not only growing social and economic problems at the local level, but also a process of devolution of institutional responsibility from central to local governments, and important cuts in central funding. Our analysis is based on an empirical investigation carried out between 2009 and 2016 in six major European cities: Barcelona, Copenhagen, Lyon, Manchester, Milan, and Munich. What clearly emerges from the research is that European cities may still show a certain capacity to innovate and govern economic changes and social challenges only if supported by an enabling MLG system.